The Walloon farmers position differently their ideal dairy production system between a global-based intensive and a local-based extensive model of farm - Dalcq, Anne-Catherine; Dogot, Thomas; Beckers, Yves; Brostaux, Yves; Froidmont, Eric; Vanwindekens, Frédéric; Soyeurt, Hélène (PloS one, 2020)
Dairy farming systems are evolving. This study presents dairy producers’ perceptions of their ideal future farm ( IFF ) to ensure revenue, and attempts to determine the reasons for this choice, the environmental aspects related to this choice, the proximity between the current farm and the IFF and the requirements for reaching this IFF. Just before the end of the European milk quota, a total of 245 Walloon dairy producers answered a survey about the characteristics of their IFF and other socio-environmental-economic information. A multiple correspondence analysis ( MCA ) was carried out using seven characteristics of the IFF (intensive vs . extensive, specialised vs . diversified, strongly vs . weakly based on new technologies, managed by a group of managers vs . an independent farmer, employed vs . familial workforce, local vs . global market, standard vs . quality-differentiated production) to observe the relationships between them. Based on the main contributors to the second dimension of the MCA, this axis was defined as an IFF gradient between the local-based extensive ( LBE ) producers (26%) and the global-based intensive ( GBI ) producers (46%). The differences of IFF gradient between modalities of categorical variables were estimated using generalised linear models. Pearson correlations were calculated between the scores on the IFF gradient and quantitative variables. Finally, frequencies of IFF characteristics and the corresponding characteristic for the current situation were calculated to determine the percentages of “unhappy” producers. Some reasons for the choice of IFF by the producers have been highlighted in this study. Environmental initiatives were more valued by LBE than GBI producers. Low similarity was observed between the current farm situation of the respondents and their IFF choice. LBE and GBI producers differed significantly regarding domains of formation (technical and bureaucratic vs . transformation and diversification respectively) and paths of formation (non-market vs . market respectively). Two kinds of farming systems were considered by dairy producers and some socioeconomic and environmental components differed between them.